Upaya Meningkatkan Hasil Belajar PAKBP Tema Hak dan Kewajiban Melalui Permainan Ular Tangga pada Fase C di SDN 07 Sintang - Albertus Agung Kurniawan; Wuriningsih Fr; Budi Hartana Nikolaus (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This research aims to improve learning outcomes and the character of the Pancasila Student Profile (P3) in the critical reasoning dimension through the application of the Problem Based Learning (PBL) learning model with the help of snakes and ladders interactive media in the subjects of Catholic Religious Education and Character. The research was conducted in two cycles at SDN 07 Sintang with material on rights and obligations as well as pride as an Indonesian nation. Cycle I was carried out on September 12 2024 for 3 x 45 minutes. Based on the results of the first cycle of observations, it appears that the character of the Pancasila Student Profile in the critical reasoning dimension has emerged, but still needs improvement. There is one student in the advanced category, five students are proficient, six students are eligible, and one student is developing. The average post-test score for cycle I reached 73. In cycle II, which was also held on September 12 2024, there was a significant increase in critical reasoning character and learning outcomes. There is increased interaction between teachers and students as well as between students, which encourages better understanding of the material. The average post-test score increased to 83, with an increase of 10% for students who needed more attention. Thus, the use of PBL assisted by snakes and ladders media has proven to be effective in improving learning outcomes and student character in the subjects of Catholic Religious Education and Character